A responsabilidade social como resposta do sistemas S ao ambiente institucional brasileiro pós-década de 1990: o caso do SESC - Rego, Mauro Lopez (2002)
Analysis of the influences exerted by the Brazilian institutional scenario on SESC ¿ The Social Service of Commerce, focusing state-market-society relations in the 1990 decade, states the core issue of the present dissertation. It also aims to discuss the suitability of adopting corporate social responsibility oriented actions in accordance with these changes. In the first place SESC's institutional setting, and questions addressed to it, as well as pressures to which the organization has been submitted since the mid 1980's are presented to the reader. Following, elements of particular significance closely related to SESC's present institutional framework are described: the country's political redemocratization, social and organizational networks, state reform, and the like.